MODERATING ROLE OF ORGANIZATIONAL CULTURE BETWEEN THE RELATIONSHIP OF KNOWLEDGE MANAGEMENT AND ORGANIZATIONAL EFFECTIVENESS - Nisar, Qasim Ali; Abbas, M. Azeem; Hayat, Khizar (International Journal For Research In Business, Management And Accounting, 2018)
The purpose of this study is to examine the effect of knowledge management practices on organizational effectiveness by considering the moderating role of organizational culture. Questionnaire survey method was used to collect the data from different employees in health sector. Sample of 450 questionnaires were distributed by applying simple random sampling technique with a response rate of 86%. Results of study shows that Knowledge Management practices has strong positive and significant relationship with organizational effectiveness whilst this association is significantly moderated by the organizational culture. Knowledge management practices alongside with favorable culture are incorporated to improve the organizational effectiveness and managers should consider these techniques. At the end of this paper, limitations of research, implications and suggestions for future research have also been highlighted.